일부 여자 중학생 대상 사회인지이론기반 영양교육 프로그램의 적용 및 효과 - 김지혜(Jihea Kim); 우태정(Taejung Woo); 이경애(Kyoung Ae Lee); 이승민(Seung Min Lee); 이경혜(Kyung-Hea Lee) (Korean journal of community nutrition, 2016)
Objectives: The purpose of this study was to evaluate the effect of nutrition education using materials based on social cognitive theory. Education topics focused on improving health-related and dietary self-awareness and behavior capability in adolescents. Methods: Participants were recruited from a middle school for girls; 67 students (educated group, n=34 and control group, n=33) participated. The education group received 12 lessons in club activity class. Self-administered surveys were conducted for each group before and after the nutrition education program. The questionnaires consisted of variables such as self-efficacy, outcome expectation, outcome expectancy, knowledge, and dietary practices based on the social cognitive theory. Education satisfaction was evaluated using a five-point Likert scale for two sections: a) teaching and learning and b) education results. The data were analyzed using a t-test and Chi Square-test (significance level: p < 0.05). Results: In the education group, post-education, there were significant differences in self-efficacy (p < 0.05), knowledge (p < 0.01), and dietary practices (p < 0.05), whereas outcome expectation and expectancy did not show any significant differences. None of the variables showed any significant differences in the control group. Educational satisfaction scores were $4.38{±}0.12$ (teaching and learning) and $4.14{±}0.15$ (education results). Conclusions: This study showed that improving adolescent's awareness and behavior capability has a positive effect on their dietary practices. Moreover, this study suggested that a theory-based determinant should be considered to improve dietary behavior among adolescents.